Persepsi Guru PAI dalam Mengintegrasikan Asesmen Diagnostik pada Kurikulum Merdeka di SDN 23 Tanete - Yuliani Yuli; Bisma Pratama; Anita (Jurnal PGSD Universitas Lamappapoleonro, 2026)
Abstract. This study aims to comprehensively analyze the perceptions of Islamic Religious Education (IRE) teachers regarding the integration of diagnostic assessment into the Merdeka Curriculum at SDN 23 Tanete, as well as to identify the supporting factors and obstacles they face. The research method used was descriptive qualitative. Data collection was conducted through in-depth interviews, non-participant direct observation, and analysis of documents such as teaching modules and student worksheets. The results of the study indicate that PAI teachers’ perceptions fall into the positive and adaptive categories. Teachers understand the importance of mapping students’ initial abilities and psychological characteristics, which implies a shift in the teaching paradigm from a content-oriented approach to a student-centered one through differentiated instruction. The success of this integration is supported by teachers’ high pedagogical motivation as well as the school’s supportive policies through the Teachers’ Working Group (KKG) forum and self-directed training. However, its implementation is still hampered by varying time constraints in developing assessment instruments, a lack of technical understanding in analyzing non-cognitive data, and a scarcity of supporting digital tools. This study recommends the need for digital-based, application-oriented assessment training for PAI teachers, as well as the institutionalization of collaborative efforts to develop a diagnostic question bank to improve work efficiency in the field. Abstrak. Penelitian ini bertujuan untuk menganalisis secara komprehensif persepsi guru Pendidikan Agama Islam (PAI) dalam mengintegrasikan asesmen diagnostik pada Kurikulum Merdeka di SDN 23 Tanete, serta mengidentifikasi faktor pendukung dan penghambat yang dihadapi. Metode penelitian yang digunakan adalah kualitatif deskriptif. Pengumpulan data dilakukan melalui wawancara mendalam, observasi langsung secara non-partisipan, dan analisis dokumen seperti modul ajar dan lembar kerja siswa. Hasil penelitian menunjukkan bahwa persepsi guru PAI berada pada kategori positif dan adaptif. Guru memahami pentingnya pemetaan kemampuan awal dan karakteristik psikologis siswa, yang berimplikasi pada pergeseran paradigma mengajar dari berorientasi materi menjadi berpusat pada siswa melalui pembelajaran berdiferensiasi. Keberhasilan integrasi ini didukung oleh motivasi pedagogis guru yang tinggi serta kebijakan suportif sekolah lewat forum Kelompok Kerja Guru (KKG) dan pelatihan mandiri. Namun, implementasinya masih terhambat oleh keterbatasan waktu penyusunan instrumen yang bervariasi, kurangnya pemahaman teknis dalam menganalisis data non-kognitif, serta minimnya perangkat digital pendukung. Penelitian ini merekomendasikan perlunya pelatihan aplikatif berbasis digitalisasi asesmen bagi guru PAI serta pelembagaan kolaborasi penyusunan bank soal diagnostik untuk meningkatkan efisiensi kerja di lapangan.